Sensitivity to Auditory Spectral Width in the Fetus and Infant – An fMEG Study - Muenssinger, Jana; Matuz, Tamara; Schleger, Franziska; Draganova, Rossitza; Weiss, Magdalene; Kiefer-Schmidt, Isabelle D.; Wacker-Gussmann, Annette; Govindan, Rathinaswamy B.; Lowery, Curtis L.; Eswaran, Hari; Preissl, Hubert (Frontiers in Human Neuroscience, 2013)
Auditory change detection is crucial for the development of the auditory system and a prerequisite for language development. In neonates, stimuli with broad spectral width like white noise elicit the highest response compared to pure tone and combined tone stimuli. In the current study we addressed for the first time the question how fetuses react to “white noise”-(WN) stimulation. Twenty-five fetuses (Mage = 34.59 weeks GA, SD ± 2.35) and 28 healthy neonates and infants (Mage = 37.18 days, SD ± 15.52) were tested with the 1st paradigm, wherein 500Hz tones, 750Hz tones and WN segments were randomly presented and auditory evoked responses (AERs) were measured using fetal magnetoencephalography (fMEG). In the 2nd paradigm, 10 fetuses (Mage = 25.7 weeks GA, SD ± 2.4) and 6 healthy neonates (Mage = 23 days and SD ± 6.2) were presented with two auditory oddball conditions: Condition 1 consisted of attenuated WN as standard and 500Hz tones and WN as deviants. In condition 2, standard 500Hz tones were intermixed with WN and attenuated WN. AERs to volume change and change in spectral width were evaluated. In both paradigms, significantly higher AER amplitudes to WN than to pure tones replicated prior findings in neonates and infants. In fetuses, no significant differences were found between the auditory evoked response amplitudes of WN segments and pure tones (both paradigms). A trend towards significance was reached when comparing the auditory evoked response amplitudes elicited by attenuated WN with those elicited by WN (loudness change, 2nd paradigm). As expected, we observed high sensibility to spectral width in newborns and infants. However, in the group of fetuses, no sensibility to spectral width was observed. This negative finding may be caused by different attenuation levels of the maternal tissue for different frequency components.